2019
DOI: 10.3389/feduc.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Talk: The Ubiquity of Feedback

Abstract: Classroom interactions play an important role in the learning and teaching of mathematics, and feedback emanating from these interactions is a powerful tool for enhancing student learning. These exchanges have been widely studied in higher education, but very few investigations have been carried out at the level of elementary students and teachers. This study aimed to contribute to existing knowledge of feedback, and to formulate guidelines to improve teacher feedback in elementary school. The specific objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
6
0
4
Order By: Relevance
“…Most teachers were aware of student errors and corrected them without necessarily discussing why those errors occurred and how they could be prevented. Such practices support Monteiro et al (2019) who noted that most of the teacher feedback focused on the task level (correcting the error) rather than discussing the underlying process level. In particular, the exploratory case studies to some extent support the descriptive results that teachers in the experimental group responded more positively to student errors than teachers in the control group.…”
Section: Students' Anxiety In Error Situationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Most teachers were aware of student errors and corrected them without necessarily discussing why those errors occurred and how they could be prevented. Such practices support Monteiro et al (2019) who noted that most of the teacher feedback focused on the task level (correcting the error) rather than discussing the underlying process level. In particular, the exploratory case studies to some extent support the descriptive results that teachers in the experimental group responded more positively to student errors than teachers in the control group.…”
Section: Students' Anxiety In Error Situationsmentioning
confidence: 75%
“…In general, classroom practice consists of student-teacher interactions that include feedback exchanges on how students' can correct their errors in order to achieve the desired learning outcomes (Monteiro et al, 2019). Rach et al (2013) postulated that four practices are essential for effective learning from errors: (1) becoming aware of the error (error awareness) so as to identify or describe the error (error identification), (2) understanding the error or explaining it (error analysis), (3) correcting the error (error correction), and (4) developing strategies for avoiding similar errors in the future (error prevention).…”
Section: Teacher Error Handling Strategies In Mathematics Classesmentioning
confidence: 99%
“…When students demonstrate their engagement through on-task behaviours, questions, or completed work, they often elicit reciprocal engaging reactions from teachers. Research has shown that when students are engaged, their teachers tend to provide them with more motivational support and assistance (Furrer & Skinner 2003;Monteiro, Mata, Santos, Sanches & Gomes, 2019;Skinner et al, 2009). SUPPORTING STUDENTS' SCHOOL ENGAGEMENT Voelkl (2012) theoretical model suggest that contextual facilitating conditions (as teachers' use of effective feedback) contributed to students' identification with school, and that this identification contribute for their behavioural engagement in the school activities, leading to academic achievement and attainment.…”
Section: Teachers' Feedback School Identification and Behavioural Eng...mentioning
confidence: 99%
“…For example, Gentrup et al (2020) observed that teachers communicate their expectations through different feedback practices, giving less positive feedback and more negative feedback to students for whom they have low expectations. Furthermore, Monteiro et al (2019) observed that teachers gave less feedback at the process and self-regulation levels to students with low achievement. In Santana's study (Santana, 2019), a number of Portuguese school directors admitted that teachers tend to ignore retained students.…”
Section: Discussionmentioning
confidence: 99%